Analysis of transformational leadership on organizational citizenship behavior with job satisfaction as an intervening variable - M. Yusron; Asro Asro (Institute of Accounting Research and Novation (IARN), 2025)
This study examines the influence of transformational leadership on organizational citizenship behavior (OCB) with job satisfaction as an intervening variable. Using a quantitative approach and PLS-SEM, data were collected from 92 employees in PT Lung Cheong Brothers Industrial. The results reveal that transformational leadership has a positive and significant effect on both job satisfaction and OCB. Moreover, job satisfaction is positively associated with OCB and functions as a significant mediator in the relationship between transformational leadership and OCB. These findings confirm that transformational leaders, through inspirational motivation, intellectual stimulation, idealized influence, and individualized consideration, not only directly enhance employees’ extra-role behaviors but also foster higher job satisfaction, which in turn strengthens OCB. The study contributes theoretically by reinforcing Social Exchange Theory and expanding its relevance in the context of developing countries. Practically, it highlights the importance for organizations to invest in leadership development programs and strategies that enhance employee satisfaction to encourage sustainable OCB. Limitations of this study include its relatively small sample size, reliance on self-reported data, and exclusion of other potential variables such as organizational culture. Future research should consider larger samples, longitudinal designs, and additional mediating or moderating variables to further enrich the understanding of these relationships.